Indigenous markets for dairy products in Africa: Trade-offs between food safety and economics - Omore, Amos O.; Staal, Steven J.; Kurwijila, Lusato R.; Osafo, E.; Aning, G.; Mdoe, N.S.Y.; Nurah, G.K. (Utrecht University, 2001)
This paper describes specific dairy marketing studies in Kenya, Ghana and Tanzania aimed at assessing public health risks from informally marketed milk and examines the economic trade-offs that policy makers should consider. Preliminary results from Kenya are presented and recommendations on cost-effective and practical interventions to improve milk safety made.